EFFECT OF PH ON GROWTH, PROTEIN PROFILS AND ANATOMY OF PLECTRANTHUS AMBOINICUS EXPLANTS: Pharmaceutical Science-Biotechnology - MOHAMED M. EL-ZEFZAFY; WALID.W. MOHAMED; MOHAMED S. BOGHDADY (International Journal of Life Science and Pharma Research, 2022)
In this study shoot tips of P .amboinicus family Lamiaceae, were used as explant for culture in which different levels of MS(Murasige and Skoog) medium salt strength and different pH media were used. Results clearly showed that, the best nutrient media for P .amboinicus propagation in establishment of shoot formation via tissue culture was 1/10 MS salt strength medium supplemented with 75 mg/L sodium dihydrogen phosphate (NaH2PO4), 30g/L sucrose, solidified with 5 g/L agar and in presence of plant growth regulator (BA 0.1 mg/L) compared to other used treatments. Treatment with pH 5 was the best pH used for P. amboinicus planted in greenhouse; on the contrary, pH 13 decreased all the tested parameters. It was appeared clearly that, pH 4 treatment enhanced the formation of two new polypeptides (30 and 60 kDa) proteins. In contrast, synthesis of these proteins was negatively affected by the other used treatments. It was clear that pH value stress induced variations in the appearance of new protein bands and disappearance of others high molecular weights proteins, whereas no changes in low molecular weights proteins were observed. On the other hand, pH 5 induced increase in the thickness of both midvein and lamina of leaf blades of P. amboinicus. It worth noting that, the thicker lamina induced by pH 5 was mainly due to increase in thickness of chloranchyma tissue, despite the presence of a decrease in the thickness of the upper epidermis. Also, the main vascular bundle of the midvein was increased in size the increment was mainly due to the increase in the length midvein bundel than control.